EFEK PEMBERIAN EKSTRAK KAYU AKWAY (Drymis Sp) TERHADAP KUALITAS SPERMATOZOA MENCIT (Mus musculus L): The Effect of Akway Wood Extract (Drymis Sp) on The Mice (Mus musculus L) Spermatozoa Quality - Angelina N. Tethool; Purwaningsih Purwaningsih (Fakultas Peternakan Universitas Papua, 2019)
This research was aimed to study the effect of Akway wood (Drymis Sp) extract treatment on spermatozoa quality of mice (Mus musculus L). The extract was given orally once a day in 2 weeks. The animals were divided into three groups; one control group (K1) and two treatment groups with four replicates. K2 group was given 1.3 ml/gr body weight / day and K3 group was given 3.3 ml/ gr body weight / day. The results indicated that treatments were increased significantly (P<0.05) on acrosome integrity and viability, while on the motility, concentration and abnormality treatments had no significant effect.